Pengaruh Kebijakan Dividen terhadap Laba di Masa Depan - Wahyu Purna Anggara, I Wayan Gde (E-Jurnal Akuntansi, 2020)
This study uses Lintner's (1956) dividend policy estimation model to examine the effect of earnings and earnings. Leverage on dividend policies. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange between 2014 and 2016. Sampling was carried out by purposive sampling technique, which then took 52 sample companies with 139 observations for the first stage analysis and 46 sample companies with 79 observations. for analysis at the second stage. This study fulfills the classical assumption test which is required as a condition for conducting multiple linear regression analysis. The results of the analysis show that dividend policy has no positive effect on future earnings. This study uses Lintner's (1956) dividend policy estimation model to examine the effect of earnings and earnings. Leverage on dividend policies. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange between 2014 and 2016. Sampling was carried out by purposive sampling technique, which then took 52 sample companies with 139 observations for the first stage analysis and 46 sample companies with 79 observations. for analysis at the second stage. This study fulfills the classical assumption test which is required as a condition for conducting multiple linear regression analysis. The results of the analysis show that dividend policy has no positive effect on future earnings. Keywords: Estimation Model; Dividend Policy; Profit; Leverage; Future Profits.